(3GdJdhjM Edi cTa ZhGeV GdJfbjMs - (3GdJaJGRGfi , eSYhO Hf YeQs; (3YHjO Gddg Hf eSYhO Hf eMehO Hf CMeO GdeMHhHj GdHNGQj GdMfaj, UOQ GdTQjYIs ((3YHO GdQMef Hf YHO GdeLjO s)
(3ChdgG (B:s
(3hHYO aEf Yde GdCUhd GdLGeY Hjf gh Ef cJGH GdJfbjM eY TQMg GdeSei HGdJhVjM s
(3BNQgG (B:s
(3dCf GdeGd eYUhe MbkG dUGMHg adGjSbW eMGd hgPG GdMce eYdhe s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3CUhd Gdabgs